Spatial distribution and stability mechanisms of soil organic carbon in a tropical montane rainforest - Wenjie Liu (Elsevier, 2021)
Estimation of soil organic carbon (SOC) storage and its dynamics in tropical montane forests is crucial for climate change prediction, which calls for further investigation into the spatial variation in SOC and its stability mechanisms. In this study, 60 subplots (20 m × 20 m) were randomly selected within a 60 ha tropical montane rainforest dynamic monitoring plot located in southern China. The physical (HFC and LFC) and chemical fractions of SOC (alkyl C, O-alkyl C, aromatic C and carbonyl C), microbial biomass carbon and other soil properties at depths of 0–10 cm, plant species and root biomass (0–10 cm and 10–20 cm) were investigated. Geostatistical methods, multiple regression trees and redundant analysis were used to reveal that the spatial variations in SOC and its stability mechanisms with the terrain. The results show that the spatial variations in HFC and the ratios of alkyl carbon/O-alkyl carbon had a moderate spatial dependence due to the complex terrain. High SOC and its physical stability fractions (HFC) were distributed along ridgelines, while the chemical stability index of SOC (alkyl C/O-alkyl C) was the highest on hillsides and in valleys. Terrain convexity best explained the spatial variations in SOC and HFC, while total nitrogen and convexity together best explained the spatial variation in the chemical fractions of SOC. Abiotic factors explained more of the variation in SOC and its fractions than biotic factors, while abiotic and biotic factors were covariant. The specific factors controlling the distribution of SOC and its fractions differed with the types of micro-terrain. These results highlight the influence of terrain on the distribution and accumulation of SOC in tropical forest ecosystems. Hence, terrain should be considered a key factor in biogeochemical models.